Hangry a startup journey - Evans, Mike. (New York Legacy Lit, 2022)
While dreaming of an easier way to order pizza, Mike Evans founded the online food delivery site, Grubhub, in his basement and grew it into the multi-billion-dollar colossus that is now a household name. But it wasn't as easy as searching, clicking, and checking out. Mike's meteoric rise to the top of the booming tech and business world demanded a decade of 80 hour work weeks, endless financing rounds, cliffhanger acquisitions, the near collapse of his collaterally-damaged marriage, a brutally difficult merger, and a pair of tumultuous I quit/unquit moments, all to steer the company to its successful IPO. And then, at the height of his success, he scrapped it all-leaving Grubhub behind and finding a new path as an entrepreneur, literally, on a solo bike ride across America. HANGRY is the unveiled and unfiltered rags-to-riches story of how Grubhub came to exemplify the promise of tech and the gig worker economy, and how it failed to live up to its impressive potential, even as it threatened Evans's sanity and marriage. "I'd created Frankenstein," Evans writes"-
Keywords: Grubhub (Firm)